Das Erzbistum des Method Lage, Wirkung und Nachleben der kyrillomethodianischen Mission - Eggers, Martin (Slavistische Beitraege, 1996)
In the series Slavonic Contributions Slavic dissertations of German-speaking countries as well as occasionally also American, English and Russian are published. In addition, the series provides a forum for anthologies and monographs of established scientists.